Rethinking teacher education : a mentoring model : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Norsworthy, Beverley Elizabeth (Massey University, 1995)
This thesis explores concerns about the quality of traditional teacher training particularly in relation to preparation of teachers for schools committed to the provision of a coherent world and life view1. Examples of such schools in New Zealand would include Kura Kaupapa, Fundamental Christian, Catholic, Seventh Day Adventist, Rudolph Steiner, Montessori. A consideration of the nature of the teaching task provides an understanding of the importance placed on the development of a coherent world and life view and the concept of educator as role model. These understandings are seen to apply to lecturers and associate teachers in the pre-service programme as well as to the trainee teacher involved the school classroom. The current image of teacher education programmes is shown to be negative and the clear call to change in areas of content, emphasis, and setting is presented. Areas of concern are identified and the conclusion is reached that this 'call for change' is not something to be ignored, but rather, to be considered and responded to with implementation of appropriate changes. It is suggested that the best way in which to respond to the call for change is through a teacher preparation programme which has a much increased component in the school. In consideration of the literature about school-based teacher preparation it becomes very clear that one key component is the role and training of the Associate Teacher. Models of preparation which are based on concepts such as Mentor, Lead Teacher and Coach are compared and important characteristics are subsequently identified. Other factors deemed to be important to training are relationships, critical and reflective thinking, and experience in the classroom setting. The thesis concludes that while a more effective teacher preparation programme would not be solely conducted or based in a school, major changes to the role of initial training, philosophy, the importance of meaning and the provision of role models must be considered. Support is given for a training programme based on a coherent philosophical foundation with significantly increased time in schools, in which Associate Teachers are involved as key players. Such a course provides experience in the 'real world' of teaching as a base to which the trainees, with the help of teacher educators, can bring theory. Combined with critical and reflective thinking, this process will enable them to develop as skilled and perceptive teachers. The conclusion of this thesis is that there is potential for training excellent teachers within a model of teacher training which has significant school based components with an increased role and responsibility for the associate teacher and school. Such training is seen to simultaneously enhance the existing school staff and community. This is seen to be most appropriate for special character schools where the concept of role modelling is a key to effectiveness.
Keywords: Training of teachers; Mentoring in education